ANALISIS FAKTOR FAKTOR YANG MEMPENGARUHI PENGUNGKAPAN MODAL INTELEKTUAL PADA LAPORAN TAHUNAN PERUSAHAAN NON KEUANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Sumardi Adiman (Jurnal Akuntansi Bisnis dan Publik, 2017)
The objective of the study was to find out and to analyze the influence of a company’s characteristics on the expression of intellectual capital expressed in the annual statement of non-finance companies listed in the Indonesia Stock Exchange in the period of 2011-2012. The company’s characteristics will be viewed from market to book ratio, leverage, and company size. The samples were 50 non-finance companies listed in the Indonesia Stock Exchange; they were included in the 50 top companies with the largest income, according to Fortune magazine, in the period of 2011-2012. The samples were taken by using purposive sampling technique. Dependent variable was the expression of intellectual capital which was measured by the number of items expressed, compared with the other indicators, while independent variables were market to book ratio proxied by total PER, leverage proxied by total DER, and company sized proxied by total Assets. The hypothesis was tested by using multiple linear regression analysis. The result of the study showed that market to book ratio and leverage did not have any influence on the expression of intellectual capital, while company size had the influence on the expression of intellectual capital in the annual statement of non-finance companies listed in the Indonesia Stock Exchange in the period of 2011-2012.